2020
DOI: 10.1371/journal.pone.0229031
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of HER2 mRNA expression by RNA in situ hybridization in canine mammary gland tumors: Comparison with immunohistochemistry analysis

Abstract: Spontaneously occurring canine mammary gland tumors share many features with human breast cancer, including biological behavior and histologic features. Compared to transgenic murine model, canine models have advantages including naturally occurring models of human diseases and cancer. In humans, breast cancer is divided into molecular subtypes based on ER, PR, and HER2 expression. In contrast with humans, few studies have evaluated these subtypes in canine mammary gland tumors, including expression of HER2. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…CK5/6 and EGFR help in the identification of basaltype tumors with aggressive behavior (48). The establishment of HER2-overexpressing tumors in dogs is challenging because HER2 overexpression is generally associated with the absence of HER2 genomic amplification (49,50). HER2 alterations in normal mammary cells were demonstrated previously using chromogenic in situ hybridization (CISH) (50).…”
Section: Discussionmentioning
confidence: 99%
“…CK5/6 and EGFR help in the identification of basaltype tumors with aggressive behavior (48). The establishment of HER2-overexpressing tumors in dogs is challenging because HER2 overexpression is generally associated with the absence of HER2 genomic amplification (49,50). HER2 alterations in normal mammary cells were demonstrated previously using chromogenic in situ hybridization (CISH) (50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified HER-2 in normal, hyperplastic, and dysplastic mammary tissues and found no relation with prognostic parameters such as disease-free interval (DFI), overall survival (OS), and lymphovascular invasion, suggesting that HER-2 may play a role in the proliferation of mammary tissue in female dogs, but not conclusively in its malignant transformation ( 40 ). Furthermore, in a recent publication ( 44 ), HER-2 messenger RNA (mRNA) expression was observed in neoplastic and non-neoplastic mammary tissues using a novel quantitative RNA in situ hybridization assay, which correlates with the immunohistochemistry score. Among the non-neoplastic mammary tissues (hyperplasia), all cases showed HER-2: 21.4% were classified as 1+, while 78.6% were positive (2+ and 3+) ( Figure 6 ).…”
Section: Conventional and New Clinical And Histological Approachesmentioning
confidence: 98%
“…Spontaneously occurring canine mammary tumors share some common molecular characteristics and biological behavior with that of human breast cancer (28). This would lead to the strong consideration of a canine mammary tumor model being a more appropriate or ideal model for human breast cancer (29) as opposed to a murine model, for example, which is induced and does not spontaneously occur.…”
Section: Discussionmentioning
confidence: 99%